ANALISIS IMPLEMENTASI FUNGSI MANAJEMEN DALAM MENINGKATKAN KUALITAS PENGELOLAAN ZAKAT DI BAZNAS KOTA PALEMBANG - Febri Afrido; Hilda; Erdah Litriani (Lentera Ilmu Madani, 2026)
This study aims to analyze the implementation of management functions in improving the quality of zakat management at Badan Amil Zakat Nasional Kota Palembang. This research is motivated by the importance of professional, transparent, and accountable zakat management in order to improve community welfare and strengthen muzakki trust in zakat management institutions. The study applies the POAC management function theory (Planning, Organizing, Actuating, and Controlling) proposed by George R. Terry. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the implementation of management functions at BAZNAS Kota Palembang has been carried out quite well. The planning function is implemented through the preparation of the Annual Work and Budget Plan (RKAT), the organizing function is applied through task distribution and coordination between divisions, the actuating function is carried out through systematic zakat collection and distribution processes, while the controlling function is implemented through internal supervision and the use of the BAZNAS Management Information System (SIMBA). The implementation of these management functions has a positive impact on the quality of zakat management, such as increasing zakat collection, improving muzakki trust, providing better services, and ensuring more orderly and targeted distribution of assistance to mustahik. The conclusion of this study indicates that the proper implementation of management functions can improve the effectiveness, efficiency, transparency, and accountability of zakat management at BAZNAS Kota Palembang. However, improvements are still needed in terms of report transparency, the development of productive zakat programs, the expansion of zakat collection sources, and the optimization of mustahik data collection so that zakat management can be more optimal and sustainable.